2018
DOI: 10.1080/21645515.2018.1507667
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of influenza vaccine immunization among primary healthcare providers in Dubai health authority, 2016-2017

Abstract: Although our HCPs attitude towards vaccine uptake, knowledge and practice were positive; the misconception about the vaccine remains the main reason for not being vaccinated as per our study findings. Overall, the study results raise hope of prospective increase in vaccination through educational and technical interventions and by increasing physician involvement. One suggested method would be to apply mandatory vaccination policies since voluntary vaccinations have shown lesser than satisfactory results and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…Participants with good knowledge of the safety of vaccines were more conceivable to get the vaccine. These ndings were in line with the results displayed in a study conducted in Dubai where the proportion of HCWs with good knowledge had a higher level of acceptance of vaccine [49].…”
Section: Discussionsupporting
confidence: 90%
“…Participants with good knowledge of the safety of vaccines were more conceivable to get the vaccine. These ndings were in line with the results displayed in a study conducted in Dubai where the proportion of HCWs with good knowledge had a higher level of acceptance of vaccine [49].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, only 60% of the HCWs surveyed in the South Al Batinah governorate were vaccinated for the 2018–2019 season, despite the availability of free vaccine to all HCWs at their workplaces. While vaccine coverage remains sub-optimal in Oman, it has improved since a 2009 estimate (46.4%) by Abou Gharbieh et al [ 22 ] and is higher than rates observed in some neighboring countries with free HCW vaccination programs, including an estimated 53.4% coverage reported in the Dubai Health Authority (UAE) for the 2016–2017 season [ 24 ]. In Iran, a recent survey reported a vaccination coverage of 57.7% in the capital, Tehran, in the 2015–2016 season [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Almarzooki et al reported an association between professional occupation of HCWs and vaccine uptake in the UAE, with physicians having the highest uptake, followed by nurses [ 24 ]. We also found that physicians and nurses as well as HCWs across all categories working in general medicine, emergency medicine or intensive care units were more likely or willing than others to be vaccinated and to recommend the influenza vaccine to patients.…”
Section: Discussionmentioning
confidence: 99%
“…the delay in acceptance or refusal of vaccination despite availability of vaccination services) 5 remains a pervasive issue in the general population as well as among HCWs across the globe. 6 , 7 , 8 , 9 , 10 Most of the studies investigating COVID-19 vaccine acceptance so far have assessed individuals’ intention to receive the vaccine, rather than their explicit acceptance of the vaccine once it was available. It is well recognized that intention does not always correlate with actual behavior, including for vaccination.…”
Section: Introductionmentioning
confidence: 99%